Legal Analysis Of Government In Efforts To Handl Sexual Violence Cases In Batam City - Shinta Novita Sari Silalahi; Lenny husna (International Journal of Social Welfare and Family Law, 2025)
Incidents of sexual violence in Batam City continue to pose a serious concern for both the government and the local community, demanding immediate and comprehensive responses. Despite various efforts by the government to address this issue, the prevalence of such incidents highlights the need for more effective prevention, intervention, and legal action. This article aims to assess the government's legal handling of sexual violence cases in Batam City, focusing on the legal framework and strategic actions designed to address the problem. By utilizing a legal analytical approach, this study will explore the measures implemented by the government to combat sexual violence, evaluate the role of the law in protecting victims, and analyze how the judicial system penalizes offenders. Furthermore, the article will discuss the collaboration between government authorities and the community in enhancing public awareness and addressing the root causes of sexual violence. The research emphasizes the importance of both preventative strategies and efficient legal processes to create a safer environment for all residents. The findings of this study aim to contribute to the broader discourse on combating sexual violence and improving legal responses in urban settings, with a particular focus on Batam City.